Productive WAQF business models through the integration of Islamic social and commercial finance - Syarifuddin, Ferry (Edelweiss Applied Science and Technology, 2024)
Poverty is an apparent problem in Indonesia, with the number of people living in poverty reaching 26.36 million. Islamic Social Finance (ISF), especially through productive waqf instruments, is one of the prospective solutions to overcome this problem. Although Indonesia has enormous waqf potential, waqf realisation is still very low. There are several challenges in the waqf collection process, namely low literacy or public awareness, unprofessional management, and a lack of qualified human resources (nazhir). This research aims to determine the optimal productive waqf model to be implemented in Indonesia using the Delphi ANP-BOCR method. To strengthen the research results, this study also conducted a meta-analysis as a form of robustness check and a benefits, opportunities, costs, and risks (BOCR) analysis of each model as supporting arguments. The findings of this study show that Islamic banks as a way to leverage funds for waqf are the most prioritised model. This is because Islamic banks act as intermediary institutions that have great potential for optimising the collection and management of waqf funds, which can increase economic growth. This is reinforced by the results obtained from the meta-analysis and several supporting arguments, which show that Islamic financial institutions (including Islamic banks) can improve community welfare through the utilisation of social funds (including waqf). Besides that, this research also discusses an alternative model of productive waqf through digitalisation by adopting several technologies that aim to increase efficiency, transparency, and accessibility so as to optimise the collection and management of waqf funds more effectively and efficiently.